Машинобудування як матеріально-технічна основа неоіндустріальної економіки України - Васильєва, Н.Ф.; Кавура, В.Л. (Економіка промисловості, 2014)
Досліджено процес формування матеріально-технічної основи неоіндустріальної економіки України, визначено роль, що відіграє в ньому машинобудівна галузь, і проблеми, з якими зіштовхуються машинобудівні підприємства при впровадженні інновацій, нових технологій, реалізації інноваційної продукції. Исследован процесс формирования материально-технической основы неоиндустриальной экономики Украины, определена роль, которую играет в нём машиностроительная отрасль, и проблемы, с которыми сталкиваются машиностроительные предприятия при внедрении инноваций, новых технологий, реализации инновационной продукции. The relevance of the study is based on the fact that the leading role in the formation of the material and technical basis of neo-industrial economy belongs to industry, in the structure of which the engineering industry has the largest share (12%). The purpose of the article is to explore the innovative activity of engineering industry and its influence on the formation of neo-industrial economy of Ukraine, and to draw conclusions concerning the acceleration of the process. The statistics given show a negative shift in the engineering industry, poor condition of its innovation activity, which is a consequence of a significant number of problems faced by enterprises of the engineering industry. This slows down the development of the industry as well as the pace of innovation and innovation products implementation in other sectors of the economy of Ukraine and thus inhibits the formation of neo-industrial economy.The survey has revealed that strengthening of the innovation, scientific and technological potential of engineering industry has a lifting impact on it. This would require making changes to the Tax Code of Ukraine, which would provide for a reduction of interest income tax for the engineering enterprises that invest in innovation in accordance with the size of their R&D costs; developing of the proposals for the introduction of preferential loans for the purchase of domestic innovative engineering products (IEP), as well as the exemption from customs duty and VAT on machinery, equipment, and components that are not produced in Ukraine but necessary for the technological re-equipment of domestic engineering enterprises; developing a system of incentives for entrepreneurs to use the latest achievements of domestic IEP in their production, organizing presentations to familiarize representatives of industrial enterprises with the development of research institutions concerning the research commissioned by industrial sector; conducting patent, market and marketing research at the national level in the domestic and foreign markets of intellectual, scientific and technical resources as to identify promising areas of R&D in the production of IEP, information support of engineering enterprises on the implementation of own R&D and procurement of the foreign ones; suggesting the Ministry of Education and Science of Ukraine to review and improve the system of training and retraining of personnel for the engineering industry taking into account its real needs, creating educational, scientific and industrial complexes on the basis of relevant professional and higher education institutions of the sector. As a result the proposed actions will allow accelerating the formation of neo-industrial economy of Ukraine.